Analyzing the health supply chain risks during COVID-19 pandemic: The moderating role of risk management - Courage Simon Kofi Dogbe; Faisal Iddris; Evans Duah; Patience Akuamoah Boateng; Emmanuel Mensah Kparl (Cogent Business & Management, 2023)
The outbreak of COVID-19 severely affected the achievement of the sustainable development goals. The American Hospital Association estimated an average loss of US\50.7 billion per month for US hospitals during the COVID-19 pandemic. In the less developed economies, it costs about US\52 billion per month to effectively manage COVID-19. This current study, therefore, sought to assess how risk management practices could moderate the relationship between supply chain risk and healthcare delivery, during the COVID-19 pandemic. A survey research design was adopted, with a quantitative research approach. The study adopted purposive sampling technique to select 216 respondents (senior/management members from procurement, stores/inventory, pharmacy, and administration) of the selected public hospitals. Structural Equation Modelling (SEM) was run in Amos (v.23), to estimate the path coefficients. The study concludes that supply chain risk had a significant negative effect on healthcare delivery among public hospitals in Ghana. Also, supply chain risk management had a significant positive effect on healthcare delivery among public hospitals in Ghana. Finally, it was concluded that risk management practices positively moderated the negative effect on supply chain risk on healthcare delivery.
Keywords: 650; COVID-19; healthcare delivery; public hospitals; risk management; supply chain risk